PENGARUH KONDISI PROSES TRANSESTERIFIKASI MENGGUNAKAN METODE SONIKASI TERHADAP RENDEMEN DAN MUTU ETIL ESTER MINYAK IKAN - Fatria Resti Haryani; Erliza Hambali; Ika Amalia Kartika (Jurnal Teknologi Industri Pertanian, 2023)
Fish oil is a lipid fraction that can be obtained from the extraction process of fish meat and by-products of fish processing. Generally, fish oil is in the triglyceride form, but tends to be unstable and easily oxidized, therefore fish oil is converted to the ethyl ester form which has better stability against oxidation. This study aims to analyze the effect of the transesterification process conditions using the sonication method on the yield and quality of fish oil ethyl ester produced. The design used was a Completely Randomized Factorial Design with 2 factors, there were the sonication time (10, 20, and 30 minutes) and the concentration of KOH catalyst (0.5, 1.0, and 1.5%). The results showed that the highest yield value was found in the 10 minutes and 0.5% KOH of 91.38%. The best ethyl ester quality from the data obtained was found in the 30 minutes and 0.5% KOH with a FFA value of 0.50%, acid value of 1.09 mg KOH/g, saponification value of 214.93 mg KOH/g, ester value 213.84 mg KOH/g, peroxide value 5.86 meq/kg, p-anisidin value 30.02 meq/kg, total oxidation value 40.44 meq/kg, density 0.8745 g/m3, and viscosity 4.81 mm2/s. Keywords: fish oil, transesterification, sonication